Making a Website-Based Sales Information System Application at Pepro Cloth Business - Nurfuadi, Nurfuadi (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
This study presents the development of a web-based sales information system application for Pepro Cloth. The goal is to create an efficient and easy-to-use system to improve sales processes and customer satisfaction. This application includes features for product catalog management, order processing, customer management, and sales reports. The methodology used is an agile software development approach using web technologies such as HTML, CSS, and JavaScript for the frontend, as well as PHP and MySQL for the backend. The app is responsive and accessible from multiple devices, providing a seamless user experience. Through usability testing and gathering feedback from potential users, the system met the requirements and expectations of Pepro Cloth management and customers. The results showed an increase in the efficiency of the sales process, handling manual errors, and increasing customer satisfaction. This app provides Pepro Cloth with a solid foundation to organize sales operations, manage inventory effectively and provide a seamless shopping experience for customers. Future research may explore additional system development and integration to extend the capabilities of this application. In conclusion, this web-based sales information system application provides significant benefits for Pepro Cloth in increasing sales performance and strengthening customer relationships.